Facile synthesis of ZnMoO4/AlPO4-5 nanorod composites as visible-light-driven photocatalysts and high-performance energy storage materials. Issue 12 (2nd March 2022) - Aman, Delvin; Abdel-Azim, Samira; Said, S.; Mohamed, Saad G.
Abstract : Photocatalytic degradation of PNP over single-crystalline ZnMoO4 /AlPO4 -5. Abstract : The present article describes the facile one-step hydrothermal synthesis of single-crystalline ZnMoO4 /AlPO4 -5 nanorod composites. The physicochemical properties of the synthesized materials, such as structure, morphology, and bandgap, were determined using techniques such as X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), N2 adsorption–desorption isotherms, X-ray photoelectron (XPS), ultraviolet-visible (UV-vis), and photoluminescence (PL). The XRD pattern of synthesized ZnMoO4 /AlPO4 -5 verifies the synthesis of nanocomposites. Diffuse UV-vis spectra reveal that ZnMoO4 /AlPO4 -5 nanorod composites exhibit an indirect semiconductor with an optical bandgap between 3.15 and 3.7 eV depending on Mo : Zn ratio. In comparison to pure AlPO4 -5, ZnMoO4 /AlPO4 -5 nanocrystal composites showed significantly higher photocatalytic activity for the degradation of para -nitrophenol (PNP, 0.04 g l −1 ), with 14, 99, 70, and 54% for AlPO4 -5, Mo : Zn (2)/AlPO4 -5, Mo : Zn (4)/AlPO4 -5, and Mo : Zn (6)/AlPO4 -5, respectively. This result might be attributed to the composite's efficient charge transfer and optimized electron–hole pair recombination. The supercapacitive ability of ZnMoO4 /AlPO4 -5 nanorod composites was also investigated in this work. For the prepared electrodes using AlPO4 -5, Mo : Zn (2)/AlPO4 -5, Mo : Zn (4)/AlPO4 -5, and Mo : Zn (6)/AlPO4 -5, the capacitance values were 400, 725, 450, and 481.25 F g −1, respectively, at a current density of 0.5 A g −1 . This study shows that ZnMoO4 /AlPO4 -5 nanorod composites are a potential visible-light-responsive photocatalyst. The electrochemical results further demonstrate the high capacitance of ZnMoO4 /AlPO4 -5 nanorod composites toward energy-storage applications.